Pinocchio, metafora della politica italiana - Stefano Pivato (LED - Edizioni Universitarie di Lettere Economia Diritto, 2021)
“Telling fables” has never ceased to exert a fascination on the world of Italian politics. On the pages of Il manifesto, Luigi Pintor repeatedly nicknamed Massimo D’Alema “Maximum Fox”. Others have identified Giorgio Napolitano with Mastro Cherry (Mastro Ciliegia) and Renzi with Pinocchio himself. These parallels have their origin in the early decades of the twentieth century, when children’s literature and young adult fiction were assigned a primary role in the project of enrolling young people in the ranks of the nation. Since then, “telling fables” has become a synonym for “telling lies” – and in this context, Pinocchio’s name is generally used as a substitute for “liar”. The cat and the fox have found their real-life counterparts in various well-known pairs of Italian politicians, starting with Nenni and Togliatti. In more recent times, Andreotti was often identified as the foxiest of foxes, and was paired, in different periods, with the various cats he encountered in the course of his long political career.